Internal quantum efficiency and Auger recombination in green, yellow and red InGaN-based light emitters grown along the polar direction. (March 2017) - Ngo, Thi Huong; Gil, Bernard; Damilano, Benjamin; Lekhal, Kaddour; De Mierry, Philippe
Abstract: We comparatively study the onset of photo-induced non-radiative intrinsic Auger recombination processes for red, yellow and green light emitting InGaNGaN hetero-structures grown along the polar orientation. We find a dramatic reduction of the photo excitation densities triggering the domination of Auger effect with increasing emission wavelength; that is to say in concert with the enhancement of the internal electric field in the structure. In long wavelength emitters, the internal electric field is stronger, and hence reducing the impact of the internal electric field is more critical.